What determines the Success of States in the SBIR Programme? - A. van der Vlist; Shelby Gerking; Henk Folmer (Tinbergen Institute, 2000)
This paper analyzes the interstate distribution of awards made through the SmallBusiness Innovation Research (SBIR) Program operated by the U.S federalgovernment. The main finding is that awards tend to be made to firms in centersof innovative activity, where knowledge is most easily created and spilloversbetween economic agents can occur most readily. State programs to assistprospective applicants for SBIR funding, on the other hand, appear to have hadlittle effect in overcoming this seemingly powerful factor. Thus, thepercentage distribution of awards by state has remained roughly constant sincethe inception of the program. A possible implication of these results is thatthe SBIR program may exacerbate interstate differences in economic growth to theextent that growth of states is associated with their ability to create newknowledge.
Keywords: 330; Innovationspolitik; USA